O sagrado no romance hispano-americano do século XX (The sacred in the Hispanic-American novel of the 20th century) - DOI: 10.5752/P.2175-5841.2013v11n29p279 - Trevisan, Ana Lucia (Horizonte, 2013)
This article studies the forms of representation of the sacred in the Hispanic-American novel of the 20th century and proposes a reflection on some ways of using the mythological and religious traditions by literature. The presence of sacred narratives in the literary texts of the 20th century is marked by a renewed aesthetic experience, once it does not only refer to using or re-using an exotic theme, but perceiving a potential translator of universal truths, immanent to religious texts or mythological ancestors. The present proposal offers a reflection on the peculiarities of European and Hispanic-American productions which make use of sacred themes, meaning to understand the aesthetic and historical consonances and dissonances. The aesthetic phenomenon named “mythologism”, studied by E.M. Mielietinski, can be understood as a modus operandi of the structure of the novel that joins literature and sacred texts and, in this study, serves as a basis for the discussion on the cultural diversity of Hispanic peoples expressed in their literary representations.